2013
DOI: 10.1007/s11548-013-0827-5
|View full text |Cite
|
Sign up to set email alerts
|

A haptics-assisted cranio-maxillofacial surgery planning system for restoring skeletal anatomy in complex trauma cases

Abstract: Purpose   Cranio-maxillofacial (CMF) surgery to restore normal skeletal anatomy in patients with serious trauma to the face can be both complex and time-consuming. But it is generally accepted that careful pre-operative planning leads to a better outcome with a higher degree of function and reduced morbidity in addition to reduced time in the operating room. However, today’s surgery planning systems are primitive, relying mostly on the user’s ability to plan complex tasks with a two-dimensional graphical inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 9 publications
0
34
0
1
Order By: Relevance
“…Their system provides unimanual haptic feedback, secondary hand control for camera movement, and a "snap-to-fit" interaction technique that can assist the surgeon to find an optimal fit of bone fractures. One of the differences between Olsson et al's system [17] and the system described here is that ours supports bimanual interaction; empowering both hands improves spatial understanding of the objects and further enhances the similarity to the actual surgical experience. In addition, some commercial haptic devices, including versions of Sensable's Phantom (now sold as Geomagic Touch) and Force Dimension's Delta (Force Dimension; Nyon, Switzerland), are capable of providing 6-DOF forces and torques; for example, Salisbury et al developed a 6-DOF haptic device designed for surgery-specific applications [18].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Their system provides unimanual haptic feedback, secondary hand control for camera movement, and a "snap-to-fit" interaction technique that can assist the surgeon to find an optimal fit of bone fractures. One of the differences between Olsson et al's system [17] and the system described here is that ours supports bimanual interaction; empowering both hands improves spatial understanding of the objects and further enhances the similarity to the actual surgical experience. In addition, some commercial haptic devices, including versions of Sensable's Phantom (now sold as Geomagic Touch) and Force Dimension's Delta (Force Dimension; Nyon, Switzerland), are capable of providing 6-DOF forces and torques; for example, Salisbury et al developed a 6-DOF haptic device designed for surgery-specific applications [18].…”
Section: Discussionmentioning
confidence: 69%
“…However, limitations to surgical training with a haptic feedback simulator were reported in one study; even though haptic feedback enabled a significant improvement in a laparoscopic suturing and knot-tying task with a higher learning rate, the surgeons reached a plateau after 5 h of training with the haptic device [16]. Recent work by Olsson et al reported an immersive virtual environment setup with a colocated visuohaptic display and head-tracking capabilities [17]. Their system provides unimanual haptic feedback, secondary hand control for camera movement, and a "snap-to-fit" interaction technique that can assist the surgeon to find an optimal fit of bone fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental difference of the present approach from published works with similar intentions is that the three‐dimensional bone surface geometries are simplified to curves that follow certain anatomical features. The advantage of using these curves to define the relevant contour of the target shape is that it reduces the overwhelmingly complex task of mandibular reconstruction to a manageable procedure.…”
Section: Discussionmentioning
confidence: 99%
“…presented cranio-maxillofacial surgery planning system that combines stereoscopic 3D visualization with haptic feedback [16]. The system allows the surgeons to plan the restoration of skeletal anatomy in facial trauma patients, and conduct the preliminary testing of alternative solutions for restoring bone fragments to their proper positions.…”
Section: Vision-based Surgical Planningmentioning
confidence: 99%